Dilma Rousseff e a política externa brasileira: diplomacia presidencial na UNASUL e no BRICS - Braga, Joyce Gracielle de Sousa (2017)
The management of Brazilian Foreign Policy was inscribed for many years in Itamaraty. From the government of Fernando Henrique Cardoso, the dynamic gained a new identity with a very active participation of the president in the issues of Foreign Policy. When Luiz Inácio Lula da Silva assumed the Presidency, he continued to develop active presidential diplomacy, through relations with emerging countries as well as with those from the region. With the success of Lula da Silva's management of Foreign Policy, PT party managed to be reelected and Dilma Rousseff assumes the Presidency in a context in which the multilateral initiatives BRICS and UNASUR are in progress. The challenge was to continue the Foreign Policy agenda left by her party partner, without changing the objectives, but adjusting diplomacy to the characteristics and political experiences of the new president.